THE ROLES, CHALLENGES AND BENEFITS OF INTERNAL AUDITING IN ORGANIZATIONS - Lazarus, Stanley; Lazarus, Roslin; Rajendran, Ambigai (International Journal of Accounting & Finance Review, 2021)
This research examined the roles, challenges & benefits of Internal Auditing in Organizations: Evidence from Oman. A semi-structured questionnaire based on research objectives was used to collect primary data from 141 respondents associated to various service, manufacturing and merchandising organizations in Muscat, Oman. Three areas were examined (i) Roles performed by IAD in organizations. (ii) Factors being a challenge for IA in organization. (iii) Benefits derived by organizations following internal audit practices. Factor analysis technique & T-test were applied to gauge the respondent’s perception about the three areas of this study. The factor analysis findings revealed (i) three key factors were extracted of perceived roles performed by IAD in organization, explaining 61.015% of variance. (ii)Four key factors were extracted of the perceived challenging factors for internal audit in organization, explaining 63.358% of variance. (iii)And three key factors were extracted of the perceived benefits derived by organizations as result of internal audit practices, explaining 62.559% of variance. Moreover, the result of the three hypotheses revealed a P value of p